2005
DOI: 10.1038/nature03178
|View full text |Cite
|
Sign up to set email alerts
|

The simplicity of metazoan cell lineages

Abstract: Developmental processes are thought to be highly complex, but there have been few attempts to measure and compare such complexity across different groups of organisms. Here we introduce a measure of biological complexity based on the similarity between developmental and computer programs. We define the algorithmic complexity of a cell lineage as the length of the shortest description of the lineage based on its constituent sublineages. We then use this measure to estimate the complexity of the embryonic lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 23 publications
3
68
0
Order By: Relevance
“…This finding is consistent with the hypothesis that selection for decreased cell lineage complexity played a major role in the evolution of metazoan ontogenies (17,37). Although Caenorhabditis elegans had been considered a prime example of mosaic development (38), modern investigations have demonstrated that its ontogeny is based on principles of regional specification rather than clonal organization of cell lineage (39,40).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with the hypothesis that selection for decreased cell lineage complexity played a major role in the evolution of metazoan ontogenies (17,37). Although Caenorhabditis elegans had been considered a prime example of mosaic development (38), modern investigations have demonstrated that its ontogeny is based on principles of regional specification rather than clonal organization of cell lineage (39,40).…”
Section: Resultssupporting
confidence: 82%
“…The present study reveals the simplest cell lineage (in the sense of ref. 17) known from metazoans and amounts to a major step forward in tracing evolutionary changes in cellular mechanisms that will ultimately facilitate understanding molecular mechanisms correlated with drastic changes in life history strategies.…”
mentioning
confidence: 99%
“…We can test whether sequestered germlines reduce selfish cell lineages by drawing propagules from a pre-defined region near the centre of the plate. We might even test more complex body plans where different lineages grow to different degrees [20] by shifting from a circular plate to arenas where growth is channelled in desired directions and amounts.…”
Section: General Methodologymentioning
confidence: 99%
“…Our hypothesis is that, while a traditional Boolean model is general, our tweaked (meta-Boolean) model is biologically plausible, and has several features that makes it useful in the context of currently used models. In particular, it can be used to investigate whether the inclusion of cell-cell signaling reduces the complexity of the resulting lineage descriptions, which would enable a more detailed analysis of, e.g., the suggestion of Azevedo et al (2005).…”
Section: Modelling the Caenorhabditis Elegans Cell Lineagementioning
confidence: 99%
“…Finally, Azevedo et al (2005) use a Boolean rule-based model to measure cell lineage complexity. They compare the complexity of the C. elegans lineage and three other metazoan lineages, and also use the measure on random lineages.…”
Section: Modelling the Caenorhabditis Elegans Cell Lineagementioning
confidence: 99%